2021
DOI: 10.1101/2021.05.27.446068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing conserved mechanisms of neurodegeneration in a colonial chordate

Abstract: Loss of the brain's functional ability is a common symptom of aging and neurodegenerative diseases. While the genetic and molecular mechanisms underlying human neurodegeneration are studied in-depth, very little is known about the evolutionary origin of these traits and their involvement in loss of nervous system function in aged invertebrate species. Here we study evolutionarily conserved elements of brain degeneration using the colonial chordate model species Botryllus schlosseri. B. schlosseri reproduces bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Among colonial ascidians, Botryllus schlosseri is one of the reference colonial species. Several features make B. schlosseri an excellent model organism (Figure 1f,g)-namely, (i) it is abundant in shallow waters and easily cultured in the laboratory; (ii) its genome and transcriptome are available (Voskoboynik et al 2013a(Voskoboynik et al , 2013bCorey et al 2016;Campagna et al 2016;Kowarsky et al 2021;Voskoboynik et al 2020;Anselmi et al 2021); (iii) asexual reproduction results in identical individuals, facilitating the ability to separate one colony (genotype) into several clonal replicates (Manni et al 2007(Manni et al , 2014Kowarsky et al 2021); (iv) it naturally forms chimeras, which allow lineage tracing by DNA fingerprints (Stoner and Weissman 1996;); (v) its transparent tissue allows in vivo tracing of labeled cells Rinkevich et al 2013;.…”
Section: Ascidians As Model Organisms For Developmental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among colonial ascidians, Botryllus schlosseri is one of the reference colonial species. Several features make B. schlosseri an excellent model organism (Figure 1f,g)-namely, (i) it is abundant in shallow waters and easily cultured in the laboratory; (ii) its genome and transcriptome are available (Voskoboynik et al 2013a(Voskoboynik et al , 2013bCorey et al 2016;Campagna et al 2016;Kowarsky et al 2021;Voskoboynik et al 2020;Anselmi et al 2021); (iii) asexual reproduction results in identical individuals, facilitating the ability to separate one colony (genotype) into several clonal replicates (Manni et al 2007(Manni et al , 2014Kowarsky et al 2021); (iv) it naturally forms chimeras, which allow lineage tracing by DNA fingerprints (Stoner and Weissman 1996;); (v) its transparent tissue allows in vivo tracing of labeled cells Rinkevich et al 2013;.…”
Section: Ascidians As Model Organisms For Developmental Studiesmentioning
confidence: 99%
“…Comparing the number of neurons in the brains of young and old colonies, they found that aged brains contain fewer cells. In both weekly degeneration cycles and overall B. schlosseri aging, they observed that the decrease in the number of neurons correlates with reduced response to stimuli and with significant changes in the expression of genes for which the mammalian homologous are associated with neural stem cells and neurodegeneration pathways (Anselmi et al 2021). Among the 411 putative homologous genes that correlate with neurodegenerative diseases (including Alzheimer's, Parkinson's, and dementia), that are expressed in the B. schlosseri brain, 71 are differentially expressed between early and late cycle, and 157 are differentially expressed between young and old colonies.…”
Section: Stem Cell Agingmentioning
confidence: 99%
“…A subsequent CNS study (Anselmi et al 2021) characterized brains from diverse developmental stages and ages, discovering that each week the number of neurons in the zooid brain fluctuates, reaching a maximum of ~1000 cells, and thereafter decreasing while the number of immunocytes increases. Comparing the number of neurons in the brains of young and old colonies, they found that aged brains contain fewer cells.…”
Section: Stem Cell Agingmentioning
confidence: 99%
“…By utilizing the solitary tunicate Polycarpa mytiligera ’s natural ability to regenerate all its body organs and tissues, including a simple brain and CNS, from a small body fragment [ 6 ], we have gained insight into neuroregeneration in a species at the base of the chordate evolutionary tree. Tunicates are basal chordates, a sister group of vertebrates, that share structures and cell types considered to be homologous to those in vertebrates [ 10 ], and are used as model systems for chordate development and regenerative studies [ 11 , 12 ]. A population of circulatory putative stem cells was suggested to mediate regeneration in this group [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While considerable progress has been made in characterization of the cellular events that lead to CNS regeneration in tunicates, only a few studies have described the expression of morphogens and their transduction pathways that stimulate cell growth, re-patterning, and diversification to regenerate the CNS [ 11 , 12 , 24 ]. To overcome this gap, we integrated transcriptome sequencing of major CNS regeneration stages with cell labeling and cell proliferation in vivo essays, to characterize the stepwise events and genetic changes that lead to whole CNS regeneration in P. mytiligera.…”
Section: Introductionmentioning
confidence: 99%